Definition of a diagnostic routine in individuals with inconclusive serology for chagas disease - Picka, Mariele Cristina Modolo [UNESP]; Meira, Domingos Alves [UNESP]; Carvalho, Thaís Batista de [UNESP]; Peresi, Eliana [UNESP]; Marcondes-Machado, Jussara [UNESP] (Brazilian Society of Infectious Diseases, 2007)
Despite the existence of highly sensitive tests, inconclusive serological results are frequent in chronic chagasic infection. This study aimed to define a diagnostic conduct for 30 individuals with inconclusive serology (G3) for chagasic infection assisted at the Outpatient Unit for Infectious and Parasitic Diseases of the Botucatu School of Medicine. Twenty-one individuals with negative serology (G1) and 33 with positive serology (G2) were also studied. Serological methods ELISA, HAI, IFI and immunoblotting TESA-cruzi were used for G1, G2 and G3, and parasitological methods xenodiagnosis, hemoculture and PCR-LIT were used for G2 and G3 individuals. ELISA, HAI and IFI were performed in 5 different blood samples in G2 and G3. TESA-cruzi was carried out only once in G1, G2 and G3 and, since it is the most sensitive, it was utilized as standard. In G3, positivity for ELISA reached 86% in the fifth blood sample; the ELISA+HAI+IFI combination showed a maximum of 44.8% in the second sample; and TESA-cruzi, 76% in one single sample. Xenodiagnosis positivity was 9.4%; hemoculture showed 15.2%; and PCR-LIT exhibited 22% positivity in G2. Nevertheless, in G3, positivity percentage was 3.4% for xenodiagnosis, 6.7% for PCR-LIT, and no positive result was found for hemoculture. In G3, PCR-LIT resolved one case which was still inconclusive according to serology tests. In order to define inconclusive diagnoses, the results suggest the combined use of ELISA+HAI+IFI in 2 blood samples, decreasing the occurrence of false positive/negative results. If results remain inconclusive, the performance of TESA-cruzi and PCR-LIT, if necessary, is recommended.
Keywords: Chronic chagasic infection; Trypanosoma cruzi; inconclusive serology; immunoblotting